Understanding the Sufism and Islamic Jurisprudence (Fiqh) Reasoning In the Terms of Religious mModeration: Perennial Philosophical Perspective - Ismail, Ismail (Madania: Jurnal Kajian Keislaman, 2021)
The truth claim phenomenon in understanding religious teachings often occurs in human life. It needs to be avoided by finding solutions. This article aimed to comprehend religious teachings using the reasoning of Sufism and Islamic jurisprudence (Fiqh) in a balanced way in order to avoid distorted understanding due to the interpretation of different religious teachings. Sufism and Fiqh reasoning are described in order to explain the meeting point between them. Sufism historically has developed since the beginning of Islam (I and II centuries H/8 AD), as well as Fiqh has developed through four periods, namely the Prophet, the Companions (Khulafaur Râsyidîn), the Ijtihad, and the Taklid period. Life requires a moderate attitude in religion. The practice of Sufism empirically is considered as a cure for mental suffering in the midst of a materialistic-hedonistic humanitarian crisis. On the other hand, the practice of Fiqh focuses on the issue of haliyah-`amliyah-furu`iyah ijtihad. At the empirical level, Sufism and Fiqh are interrelated and integrated. Therefore, there is always a meeting point that unites Sufism and Fiqh reasoning. Quoting the opinion of Imam Shafi`i "wa man jama`a bainahuma tahaqqaqa", whoever practices the two together (Sufism and Fiqh), he has correctly carried out religious teachings. Fenomena klaim kebenaran (truth claim) dalam memahami ajaran agama kerap kali terjadi dalam kehidupan manusia. Hal ini perlu dihindari dan perlu dicari solusinya. Artikel ini bertujuan memahami ajaran agama menggunakan nalar tasawuf dan nalar fikih dengan imbang guna menghindari pemahaman menyimpang akibat penafsiran ajaran agama yang berbeda. Nalar tasawuf dan nalar fikih dideskripsikan guna menjelaskan titik temu antara antar keduanya.  Secara historis, tasawuf telah berkembang sejak awal kelahiran Islam (abad I dan II H/8 M), begitu pula fikih berkembang melalui empat periode yaitu periode Nabi, periode Sahabat, periode ijtihad dan perode taklid. Kehidupan saat ini, dibutuhkan sikap moderat dalam beragama. Secara empirik, praktek tasawuf dianggap sebagai obat penyembuh penderitaan batin di tengah-tengah krisis kemanusiaan yang serba materialistik-hedonistik. Di sisi yang lain, praktek fikih menitikberatkan pada persoalan ijtihad yang bersifat haliyah-`amliyah-furû`iyah. Dalam tataran empiris antara tasawuf dan fikih keduanya saling berkait dan terintegrasi. Karenanya, antara nalar tasawuf dan nalar fikih selalu ada titik temu yang menyatukan antara keduanya.  Mengutip pendapat Imam Shafi`i “Wa man jama`a bainahuma tahaqqaqa”, siapa yang mengamalkan antara keduanya secara bersama-sama (tasawuf dan fikih) maka ia telah menjalankan ajaran agama dengan benar.